How Can Value-Added Intermediary Service Providers and Exporting Firms Co-Create Value in Bottom of the Pyramid Markets? - Khan, Huda; Zahoor, Nadia; Tarba, Shlomo Y.; Atanassova, Iva (Springer, 2025)
International business (IB) research has recently turned its attention to social innovation, whereby firms are expected to create value for under-privileged societies. We examined the roles played by manufacturing firms that export their products to bottom of the pyramid (BOP) markets and by their partnering value-added intermediary service providers located in such markets in achieving value co-creation, for the speed of social innovation. By means of a survey of Pakistani exporting firms, we found that the exporters’ communication with service intermediaries in regard to social goals and the psychological benefit of social innovation positively influences value co-creation between them. These effects are strengthened in the presence of a strongly shared vision. The co-creation of value by exporting firms and intermediary service providers mediates the effects of such communication on social innovation speed. Our findings contribute to the value co-creation perspective by validating important role played by value-adding intermediary service providers in accelerating the social innovation of emerging market exporters for BOP markets. Our study highlights the important roles played by exporters’ cross border communication and shared vision with intermediaries in the value co-creation for BOP markets. In this paper, we also discuss the managerial and policy implications of our findings.
Keywords: Social goal communications; Psychological benefit communications; Shared vision; Value co-creation; Value-adding intermediary service providers; Bottom of the pyramid; Social innovation; social innovations